IMPROVED BRAKE SYSTEM IMPROVEMENT ACTIVITIES LEARNING USING MULTIMEDIA LEARNING MEDIA CLASS XI SMK MA `ARIF 1 KRETEK YOGYAKARTA ACADEMIC YEAR 2013/2014 - Aris Kusnadi; Subagyo Subagyo (Jurnal Taman Vokasi, 2014)
Type of research is the type of Classroom Action Research (CAR). The method used in this study was a collaboration. The study was conducted in three cycles with research subjects in class XI student of SMK, amounting to 30 students. The data were obtained from the observation during learning activities take place by using observation and tests. Analysis of the data for the observation sheet is done by calculating the percentage of student activity and learning outcomes for tests performed by calculating the average value of the test. The results showed that the activity of students using multimedia learning strategy by 36% and student learning outcomes in subjects experiencing an increase in the brake system. This is evidenced by the first cycle of test results obtained by the average value of 62.16, and the achievement of a minimum completeness criteria (KKM) by 20%.Moderate activity of students in the second cycle increased to 63% and the learning outcomes gained an average of 68.83, an increase of 6.67 points from the first cycle and an increase in the achievement of the KKM to 40%. In the third cycle student activity increased to 85% and the average value also increased by 6.33 points from the second cycle and the average value becomes 75.16. Achievement KKM third cycle increased to 73.33%. Based on the results of the study, expected to subject teachers to be able to implement a multimedia learning strategies in the learning process so that the activity and student learning outcomes will increase.